Is less better?: Boot camp, regular probation and rearrest in North Carolina - Jones, Mark (American journal of criminal justice, 1997)
Using official data, 331 boot camp participants and a stratified random sample of 369 regular probationers were tracked for rearrests over a threeyear period. Chisquare tests and logistic regression analysis indicate that participation in boot camp was significantly associated with rearrest for drug offenses, offenses categorized as “other,” and all types of offenses combined. Contrary to most prior research, which suggests that boot camp participation has no effect on subsequent criminal behavior, the results in this study indicate that participation in the boot camp program had a detrimental effect on its participants.